Object deprofiling in the context of inherently causative verbs: A case study of the semantically similar verbs build, construct, and create - Baeskow, Heike (Linguistik Online, 2025)
Although there is a substantial body of literature on implicit arguments, only a few works deal with argument omission in the context of highly transitive verbs. The present study is intended to make a contribution to this understudied field. To that purpose, three semantically similar verbs of creation – namely build, construct, and create – were analysed contrastively with respect to complement omission. The analyses show that despite a certain degree of semantic overlap, these verbs differ in their disposition to leave their object argument implicit. The subtle contrasts are described on the basis of frame information, the discourse context, pragmatic/stylistic factors, aspect, and collocations as indicators of selectional preferences. Intransitive uses of the three verbs under consideration are represented as subtypes of the corresponding prototypical transitive variants. These alternants share a subset of syntactic and semantic information, including thematic entailments in the sense of Dowty (1991), which can be split into “mental” as well as “physical” information. The analyses are innovative in that they are largely based on contexts from the Concretely Annotated English Gigaword corpus, which allows users to search for syntactic structures and thus to extract intransitive uses of inherently transitive verbs.